Next-Generation Approaches Needed to Tackle Antimicrobial Resistance for the Development of Novel Therapies Against the Deadly Pathogens - Bhandari, Vasundhra; Suresh, Akash (Frontiers in Pharmacology, 2022)
The advent of antimicrobials was a miracle that saved millions of lives across the globe. With the discovery of penicillin, varieties of other antimicrobials came into play one after another. However, the injudicious use of antimicrobials for therapeutics and prophylactics and overuse in agriculture and animal husbandry industries resulted in its gloominess and rise of antimicrobial resistance. The microbes have slowly outsmarted the human race with diverse mechanisms to evade the antimicrobial effects of the drugs in use. The review aims to discuss the emergence of resistance in bacterial species with time and the various means by which bacterial cells had safeguarded themselves. In addition to that, we have also highlighted new approaches currently used to tackle antimicrobial resistance or practices that could be useful in identifying new treatment options.